Implementation of Internal Control Information System to Improve The Effectiveness of The Company's Financial Supervision - Anniza Rezky Z; F.X. Kurniawan Tjakrawala (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Effective financial supervision is an essential element in the success of a company's management. With the development of technology, the implementation of internal control information systems is increasingly becoming the main need. This study aims to analyze how the internal control information system can improve the effectiveness of a company's financial supervision. The research method used is a literature review and empirical analysis of companies implementing internal control information systems. The study results show that companies that use internal control information systems can reduce errors in financial records, increase transparency, and minimize the risk of financial fraud. This study implies that the implementation of an internal control information system can help companies improve operational efficiency and strengthen overall corporate governance, which ultimately has an impact on increasing investor and stakeholder confidence.